Effects of Plant Age, Topography and Processing System On the Biochemical Traits and Quality of Tea (Bangladesh Journal of Botany, 2021)
Laboratory experiment was conducted to study the biochemical and quality parameters of tea i.e. Polyphenol, Theaflavin (TF), Thearubigin (TR), Caffeine, Lipid, Total ash, Chlorophyll, Moisture content etc. under different variables designed for age, topography, and processing system imposed on an established tea orchard. Results revealed that plant age and topography do not have any significant effect on most of the studied parameters. In case of plant age, tannin is found to be significantly higher in mature tea plant (39.35 ppm) whereas young plant showed significantly lower total sugar content (28.98 ppm). In case of land elevation, significantly higher tannin (37.41 ppm) and lower carotenoid content (0.74 mg/g) were evident in plants from kunchi topography where flat topography showed significantly higher total sugar (26.62 ppm) in leaves. The handmade tea flavoured with significantly higher amount of polyphenol (58.57 ppm) and caffein (43.30 ppm) but industry made tea showed significantly higher amount of tannin (37.65 ppm), total sugar (15.25 ppm) and TF:TR (1:10).Bangladesh J. Bot. 50(3): 633-639, 2021 (September)